Answer:
Four, because 4/8 = 1/2 There are obviously 8 1/8ths in a whole so half of that amount is obviously 4 1/8ths.
Step-by-step explanation:
Gave above.
X² <span>+ 11x + 7
because 7 is a prime number, this doesn't factor prettily. you'll want to use the quadratic formula; if you aren't familiar with it, i'd either research it or look it up in your textbook, because it's clunky and not easily understood in this format:
(-b </span>± √((b)² - 4ac))/(2a)
in your equation x² + 11x + 7 ... a = 1, b = 11, and c = 7. what you do is you take the coefficients of every term, then plug it into your equation:
(-11 ± √((11)² - 4(1)(7))/(2(1))
not pretty, i know. but, regardless, you can simplify it:
(-11 ± √((11)² - 4(1)(7))/(2(1))
(-11 ± √(121 - 28))/2
(-11 ± √93)/2
and you can't simplify it further. -11 isn't divisible by 2, and 93 doesn't have a perfect square that you can take out from beneath the radical. the ± plus/minus symbol indicates that you have 2 answers, so you can write them out separately:
(x - (-11 - √93)/2) and (x + (-11 - √93)/2)
they look confusing, but those are your two factors. they can be simplified just slightly by changing the signs in the middle due to the -11:
(x + (11 + √93)/2) (x - (11 - √93)/2)
and how these would read, just in case the formatting is too confusing for you: x plus the fraction 11 + root 93 divided by 2. the 11s and root 93s are your numerator, 2s are your denominator.
We know: The sum of the measures of the angles of a triangle is equal 180°.
We have: m∠A =65°, m∠B = (3x - 10)° and m∠C = (2x)°.
The equation:
65 + (3x - 10) + 2x = 180
(3x + 2x) + (65 - 10) = 180
5x + 55 = 180 <em>subtract 55 from both sides</em>
5x = 125 <em>divide both sides by 5</em>
x = 25
m∠B = (3x - 10)° → m∠B = (3 · 25 - 10)° = (75 - 10)° = 65°
m∠C = (2x)° → m∠C = (2 · 25)° = 50°
<h3>Answer: x = 25, m∠B = 65°, m∠C = 50°</h3>